A Modified Flow Field in the Extrusion of Bimetallic Systems - Śliwa, R.E.; Mishuris, G.S. (Engineering Transactions, 1999)
The aim of the paper is to propose a new kinematically admissible velocity field corresponding to experimental results of the co-extrusion of various materials. A modified mathematical description of the plastic flow in the extrusion of the bi-metallic composite including boundaries of the plastic zone described by appropriate functions has been proposed. Velocities, grid distortion and strain rate distribution have been calculated by taking into account information on the plastic zone boundaries and their forms. Excellent agreement between the analytical and the experimental results of the plastic flow of longitudially oriented metal composite has been established.